Comparison of Yeast and CHO Cell-Derived Hepatitis B Vaccines and Influencing Factors in Vaccine-Naïve Adults in China: Insights for Personalized Immunization Strategies - Qian Qiu; Huai Wang; Wei Zhang (Vaccines)
Background: Various factors influence the immunologic responses to HBV vaccines in adults, including unchangeable individual characteristics. Personalized vaccination regimens accounting for host factors can enhance immune efficiency, particularly for adults at higher risk. Methods: In this two-center controlled trial, HBV vaccine-naïve participants aged 25–55 were randomly administered the two types of HBV vaccines (yeast cell-derived (YDV) or Chinese hamster ovary (CHO) cell-derived) at 0–1–6 months. Antibody titers were measured eight weeks after the final dose. Results: Overall, 289 participants with YDV and 293 participants with CHO completed the three-dose series and antibody testing. The seroprotection rates (SPRs) were comparable (97.23% vs. 98.98%; p = 0.1398), but the geometric mean concentration (GMC) was significantly higher for the CHO (1627.83 mIU/mL vs. 600.76 mIU/mL; p < 0.0001). The GMC of both regimens declined significantly in individuals aged ≥45 years and males. Unlike the YDV, the GMC of CHO was minimally affected by BMI or smoking or drinking status. Conclusion: The CHO regimen may be advantageous for HBV vaccine-naïve adults aged 25–55 with BMI ≥ 25 or those who smoke or drink, in terms of immunogenicity and durability, providing insights for personalized immunization strategies.